2019
DOI: 10.1097/qai.0000000000001958
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous HIV-1 Reactivation Patterns of Disulfiram and Combined Disulfiram+Romidepsin Treatments

Abstract: Few single latency-reversing agents (LRAs) have been tested in vivo, and only some of them have demonstrated an effect, albeit weak, on the decrease of latent reservoir. Therefore, other LRAs and combinations of LRAs need to be assessed. Here, we evaluated the potential of combined treatments of therapeutically promising LRAs, disulfiram and romidepsin.Setting and Methods: We assessed the reactivation potential of individual disulfiram or simultaneous or sequential combined treatments with romidepsin in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…This heterogeneity and the multiplicity of the silencing mechanisms underlying HIV-1 latency rather than latency in itself are now considered as the major barrier to eradicating HIV-1 (8). In agreement, LRAs have been found to present various reactivation potencies in vitro and ex vivo (45)(46)(47). In the context of DNA methylation, our previous study has highlighted that the DNA methylation inhibitor 5-AzadC exhibits different ex vivo reactivation potencies in terms of HIV-1 latency reversal (18).…”
Section: Discussionsupporting
confidence: 61%
“…This heterogeneity and the multiplicity of the silencing mechanisms underlying HIV-1 latency rather than latency in itself are now considered as the major barrier to eradicating HIV-1 (8). In agreement, LRAs have been found to present various reactivation potencies in vitro and ex vivo (45)(46)(47). In the context of DNA methylation, our previous study has highlighted that the DNA methylation inhibitor 5-AzadC exhibits different ex vivo reactivation potencies in terms of HIV-1 latency reversal (18).…”
Section: Discussionsupporting
confidence: 61%
“…Targeting and reactivating latent cells is challenging due to the heterogeneous nature of the viral reservoirs. Recent studies demonstrating diverse responses of infected cells to LRAs point to their weak effect (Archin et al, 2012;Spivak et al, 2014;Elliott et al, 2015) and highlight the diversity of determinants responsible for the reservoirs' heterogeneity that were demonstrated so far to be virus genetic background- (Norton et al, 2019), cell model- (Spina et al, 2013), cell type- (Baxter et al, 2016;Grau-Expósito et al, 2019;Kula et al, 2019), silencing mechanism- (Elliott et al, 2014;Yukl et al, 2018), tissue reservoir- (Elliott et al, 2014;Telwatte et al, 2018;Yukl et al, 2018), integration site- (Chen et al, 2017;Abner et al, 2018;Battivelli et al, 2018), patient- (Darcis et al, 2017;Yukl et al, 2018), and gender- (Das et al, 2018) specific. In addition, some studies demonstrate a heterogeneous effect of LRAs on NK cells (Garrido et al, 2016) and cytotoxic T-cell lymphocyte (Walker-Sperling et al, 2016) activity with conflicting observations, suggesting either an immunosuppressive effect or a reduced impact of LRA activity on cells sensing HIV-1 reactivation (Archin et al, 2012;Jones et al, 2014;Clutton et al, 2016;Walker-Sperling et al, 2016;Desimio et al, 2017Desimio et al, , 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the effects may also be cell type-specific. We have also recently demonstrated that disulfiram exhibited limited reactivation spectra, being active only in myeloid-derived HIV-1 latently infected cell lines (U1, THP89GFP monocytic, and CHME-5/HIV-1 microglial cells) but not in Jurkat-based T-cell lines (Kula et al, 2019). These heterogeneous cellular responses to LRAs indicate that distinct and cell-type dependent molecular mechanisms contribute to HIV-1 latency in diverse reservoirs.…”
Section: Cell Type-specific Effects Of Latency Reversing Agentsmentioning
confidence: 97%
“…LRA cocktails can either target a specific cell type or globally affect all cell types in the latent reservoir. However, it has been shown that LRA cocktails do not globally affect all latently infected cells equally [52]. To evaluate the potential that the LRAs have on latent reactivation in monocytes, we established an in vitro monocytic model of latency (TLat).…”
Section: Discussionmentioning
confidence: 99%